Attitude and Social Support Associated with Weekly Iron-Folic Acid Adherence Among Adolescent Girls in Badung, Bali, Indonesia - Gusti Ayu Putu Laksmi Puspa Sari; Ni Putu Udayana Antari; I Gusti Agung Ari Kusuma Yana; Yosi Irawati Wibowo; Adji Prayitno Setiadi; Ni Nyoman Yudianti Mendra (Indonesian Journal of Pharmaceutical Education, 2026)
Anemia among adolescent girls in Indonesia remains a significant public health problem. Attitude and social support may influence the success of anemia prevention through adherence to weekly iron–folic acid (IFA) supplementation. This cross-sectional study analyzed the association between attitude, family support, peer support, school support, and adherence to weekly IFA supplementation among adolescent girls in one junior high school in Badung, Bali, Indonesia. All eligible adolescent girls were included in the study (n = 141), and data were collected using a structured questionnaire. Univariate analysis was used to describe respondent characteristics, while bivariate analysis using the Chi-square test and Fisher’s exact test was performed to examine associations between variables. A total of 83.0% of respondents were adherent to weekly IFA supplementation. Among all respondents, 45.4% had a positive attitude, 13.5% had family support, 72.3% had peer support, and 95.7% had school support. School support was significantly associated with adherence to weekly IFA supplementation (p = 0.001), and adolescent girls who received school support had higher odds of adherence than those who did not (OR = 30.5; 95% CI: 3.4–276.2). These findings indicate that school support plays an important role in improving adherence to weekly IFA supplementation among adolescent girls. Strengthening the role of educational institutions through structured supervision and health education may enhance adherence and support anemia prevention programs in this population.